Epidermoid cyst of the head and neck - Ruggeri, Carlos S.; García Pita, Elián; Ianardi, Fabricio (Revista del Hospital Italiano de Buenos Aires, 2018)
Epidermoid cysts of the head and neck are rare and can be difficult to diagnose. Two cases of patients with epidermoid cysts of the floor of the mouth with suprahyoid extension, other located at posterolateral oropharynx wall andother located at the submandibular and submental space with extention to midline are described. They were successfully treated by a transoral and transcervical approach respectively. A review of the literature was performed, and the anatomical, clinical and histological aspects and treatment of these uncommon tumors were reported
Keywords: epidermoid cyst; neck